2009
DOI: 10.1152/ajprenal.90762.2008
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and hypertonicity modulate proximal tubular aquaporin 1 expression

Abstract: Aquaporin 1 (AQP1) is the major water channel in the renal proximal tubule (PT) and thin descending limb of Henle, but its regulation remains elusive. Here, we investigated the effect of ANG II, a key mediator of body water homeostasis, on AQP1 expression in immortalized rat proximal tubule cells (IRPTC) and rat kidney. Real-time PCR on IRPTC exposed to ANG II for 12 h revealed a biphasic effect AQP1 mRNA increased dose dependently in response to 10 Ϫ12 to 10 Ϫ8 M ANG II but decreased by 50% with 10 Ϫ7 M ANG I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…However, the HS diet in the present study showed downregulation of both mRNA and protein levels of AQP1 (Fig 5A and 7A). These observations could be due to the suppression of RAS by HS diet as Ang II has been reported to increases AQP1 expression in the proximal tubule via direct interaction with angiotensin type 1 receptor [81]. While, all the RAS components are expressed in renal proximal tubule cells [82] suppression of the function of RAS by HS diet may lead to low production of Ang II [83], which has been associated with the downregulation of AQP1 and AQP2 [79].…”
Section: Discussionmentioning
confidence: 99%
“…However, the HS diet in the present study showed downregulation of both mRNA and protein levels of AQP1 (Fig 5A and 7A). These observations could be due to the suppression of RAS by HS diet as Ang II has been reported to increases AQP1 expression in the proximal tubule via direct interaction with angiotensin type 1 receptor [81]. While, all the RAS components are expressed in renal proximal tubule cells [82] suppression of the function of RAS by HS diet may lead to low production of Ang II [83], which has been associated with the downregulation of AQP1 and AQP2 [79].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In our previous reports, we showed that changes in the expression and distribution of AQP1,4 occur during the early stages of DR. 24,25 Few studies have focused on the mechanism of how AQP1,4 changes as DR progresses. The RAS is involved deeply in the regulation of AQP1 expression in renal disorders, 26,27 and treatment with an ARB slows the progression of chronic kidney disease in patients with diabetes by regulating medullary transport proteins, including AQP2. 28 However, to our knowledge the relationship between the RAS and AQP1,4 in the central nervous system has not been investigated.…”
mentioning
confidence: 99%
“…In an immortalised rat proximal tubule cell line and in rat kidney, angiotensin II (Ang II) was able to increase AQP1 mRNA and protein expression (Bouley et al 2009). In principle, changes in dietary protein content are able to modulate Ang II concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AQP1 mRNA and protein were upregulated by extracellular hypertonicity in immortalised rat proximal tubule cells (Bouley et al 2009). Water intake of individual goats was not monitored in the current study.…”
mentioning
confidence: 99%